Implementasi Sistem Penentuan Lokasi Dalam Gedung (Indoor Localization) Menggunakan Metode Fingerprinting Berjenis Monitor Based Localization (MBL) Dengan Teknologi Bluetooth Low Energy (BLE) - Muhammad Hasbi Ash Shiddieqy; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Besides being famous for its accuracy in determining outdoor location, GPS technology also has weaknesses in determining indoor location due to signal attenuation. Therefore, to determine the indoor location, one of the methods that can be used is the fingerprinting method. The fingerprinting method is a method for determining location by classifying the obtained signal patterns into location names based on the signal characteristics at a location. . One technology that can be utilized to produce signals in the fingerprinting method is Bluetooth Low Energy (BLE) technology. BLE technology is used because it has several advantages such as fast advertisement packet duration, small device size, can use long-lasting batteries, etc. In this research, the fingerprinting method and BLE technology use the concept of Monitor Based Localization (MBL). The MBL concept is a concept where the device to be located only emits a passive signal, while other devices will determine the location. Percentage of the system error in determining location reaches 15.24% which means it has accuracy in determining location of 84.76%. The errors in determining location can be caused by the similarity of signal patterns at certain points at 2 different locations.